Work in the Intersections: A Black Feminist Disability Framework - Bailey, Moya; Mobley, Izetta Autumn (Gender & Society, 2019)
A Black feminist disability framework allows for methodological considerations of the intersectional nature of oppression. Our work in this article is twofold: to acknowledge the need to consider disability in Black Studies and race in Disability Studies, and to forward an intersectional framework that considers race, gender, and disability to address the gaps in both Black Studies and Disability Studies. By employing a Black feminist disability framework, scholars of African American and Black Studies, Women’s, Gender, and Sexuality Studies, and Disability Studies have a flexible and useful methodology through which to consider the historical, social, cultural, political, and economic reverberations of disability.
Keywords: EDI; afro-féminisme; approches et analyses; capacitisme; care; cours; discipline; féminisme afroaméricain; histoire et politique; intersectionnalité; philosophie; premier cycle; racisme; ressource en ligne; santé; sciences humaines; sex1920; sexisme; systèmes d'oppressions; thématiques; études critiques du handicap; études de genres

‘Learning the rules of the game‘: Emotional labor and the gendered academic subject in the United States - Bartos, Ann E.; Ives, Sarah (Gender, Place & Culture, 2019)
In this article, we investigate how entrenched sexism in higher education can take root in graduate school, where many of us learn the ‘rules of the academic game’ through our roles as teaching assistants (TAs). Feminist and antiracist scholars have documented how these ‘rules of the game’ are scripted on different academic bodies. We focus this article on the stubborn persistence of sexism in university life through the everyday, mundane forms of emotional labor and care that TAs feel obligated to perform. As the current #MeToo movement reminds us, sexism, sexist exploitation, and oppression are as evident today as they were decades ago when feminist scholars and activists challenged the masculinism of geographical discourse through examinations of power, knowledge, and subjectivity. Our research returns to these themes by examining TAs’ experiences of sexism in the classroom through the lens of critical care ethics. A focus on TAs brings attention to the constitution of the gendered academic subject and identifies the emotional labor required to manage this subject. We believe that the durability of sexism warrants an investigation of the sites where women learn their ‘place’ in the academy.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; care; charge émotionnelle; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sexisme; stratégie féministe; systèmes d'oppressions; thématiques; travail; universitaires; éducation; états-unis

Gouverner la vie privée: l'encadrement inégalitaire des séparations conjugales en France et au Québec - Biland, Émilie (Gouvernement en question(s), 2019)
"L'implication de l'État dans la vie privée pose problème : les individus ont davantage de droits que par le passé, mais certains de leurs comportements, jugés problématiques pour la collectivité, justifient un interventionnisme renouvelé, dans lequel acteurs privés et mécanismes de marché occupent une place croissante. En tension entre libéralisme et normalisation, cette action publique participe aux recompositions des rapports sociaux, entre les classes sociales, entre les genres, ainsi qu'entre la population majoritaire et les personnes racisées. Objet de vifs débats et de réformes récurrentes, la régulation par le droit des séparations conjugales est un observatoire précieux de ces recompositions, ici analysées à partir de trois enquêtes collectives, qualitatives et quantitatives, menées des deux côtés de l'Atlantique. En France comme au Québec, l'accès aux procédures, les interactions avec les professionnel.les et l'encadrement des modes de vie sont les trois dimensions constitutives du gouvernement de la vie privée. Cependant, chacun des contextes n'articule pas de la même manière inégalités de classe et inégalités de genre. En scrutant la production institutionnelle des inégalités privées, cet ouvrage invite à imaginer des voies alternatives, dans la sphère privée comme dans la sphère publique, pour que la politique des droits tienne ses promesses émancipatrices."
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; discours dominant; droit des femmes*; droits des femmes*; europe; famille; france; hétérosexualité; inégalités; mariage; maternité; parentalité; patriarcat; premier cycle; privilèges; périodes historiques; québec; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; sexisme; sexualité; soc2262; soc2264; sociologie; systèmes d'oppressions; séparation; thématiques